Utilização da ferramenta compute It para introdução à lógica de programação - Figueiredo, João Pedro de Morais (Universidade Federal Rural do Semi-Árido, 2019)
The present work presents a study about the use of the Compute It tool in the development of the logical reasoning of students from initial periods of courses in the area of computation that are beginning studies in the programming disciplines. The proposal is the use of the tool as a main tool in the development of logical reasoning in problem solving in algorithms. The study has been applied to the students of the Federal University of the Semi-Arid, Angicos campus, of the courses of Bachelor of Information Systems and Graduation in Computing and Computer Science, that were enrolled in the discipline of Algorithms and Programming I. The students were divided into three groups that participated in simultaneous classes on a same set of introductory concepts related to the logic of programming. The classes differed in the teaching technique used to present and exercise the concepts: exposition with Portugol, programming with the tool Visualg and interaction with the online tool Compute It. The analyzes indicated that the first results with the use of this methodology are positive, nevertheless they require monitoring for a longer period of time so that their results can be effectively proven. In this way, it is believed that this tool can enable improvements in the teaching-learning process of the programming disciplines; however, one should not overlook other teaching tools, such as lectures, since the game is a complement not an absolute method of teaching.
Monografia
Keywords: Computação; Disciplinas de programação; Compute It; Ferramenta educacional; Ensino-aprendizagem; Computing; Programming disciplines; Compute It; Educational tool; Teaching-learning; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA